Pengaruh Motivasi Kerja Dan Kepuasaan Kerja Terhadap Prestasi Kerja Pegawai Pada Kantor Pelayanan Pajak Pratama Raba Kota Bima - Yuli Yanti; Kartin Aprianti (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Human resource management is the set of organizational activities directed at attracting, developing and retaining an effective workforce. Managers have a big role in directing people who are in the organization to achieve the expected goals, including thinking about how to have human resource management that is able to work effectively and efficiently so that they have good work performance (Dikdoyo et al, 2023).